THYMUS GLAND PATTERN IN CHILDREN WITH MAURIAC SYNDROME - O. B Sirotina (Медицинская иммунология, 2014)
Thymic gland was examined in three children with Mauriac syndrome, using ultrasonographic studies. Some novel results were obtained, concerning dimensions, echostructure and vascularization of thymus in this disorder. Absence of detectable age-related thymic involution in these patients is of special interest, thus, probably, reflecting an increased functional activity of thymus in complicated cases of type I childhood diabetes, e.g., in Mauriac syndrome.